TAJDÎD FIQH DARI KONSERVATIF TEKSTUAL MENUJU FIQH PROGRESIF KONTEKSTUAL - Nasrulloh, Nasrulloh (Fakultas Syariah, 2014)
By reference to Rule (al-mashaqqah tajlib al-Taysir) and (idza dhaqa ittasa'a), the need to reconstruct the fiqh through tajdîd considered a necessity when there are difficulties to implement it. On one side there is an opinion that tajdîd should be limited to new problems that are not listed in the qath'i texts, but on the other hand argue that all texts are dzanni, so there is no limit in the realm of tajdîd and ijtihad. Through this theme, the authors also cite some of the thinking that distinguishes between authenticity of the revelation as the God‟s will and the authenticity of Hadis which is still questionable. Then, a distinction efforts also should be made between the revelation of God's will as an ideal and the truth of human understanding (fiqh) that is relative so it needs to be reconstructed in order to remain relevant anywhere and anytime.